Gershwin, Imagination and the Present Day Culture: Art Review - Adelaida Berchi Petrancu (Centre for Behaviour and Wellness Advocacy, 2016)
In this paper, I analyzed George Gershwin's musical works and the role of imagination in his musical compositions. In his case, imagination is a new product of his mind. This is in accordance with his interests, purposes and cultural backgrounds. Efforts to appreciate his works should be done in classical terms rather than using some new criteria. Failure to follow these criteria could culminate to relativism, as a result of the decreased role of imagination in today's art. This bias may lead to imitation.